Children's odor pleasantness ratings may not differ according to pubertal status: Preliminary results from a sample of 11-14-year-old Czech children - Martinec Nováková, Lenka; Plotěná, Dagmar; Havlíček, Jan (Physiology & behavior, 2024)
Puberty tends to be viewed as a "turning point" in hedonic perception of body odor (BO)-related smells. The pubertal stage, a potential proxy for the underlying physiological changes, may contribute to variation in odor hedonic perception. Other potential modulators of odor hedonics are general semantic knowledge about odors (which also tends to be subsumed under the term "age") and perceived odor intensity. The present cross-sectional study examined differences in hedonic odor perception across puberty in 205 Czech children aged 11-14 (89 boys). We investigated whether children differ in the hedonic appraisal of BO-related (16-androstenes and castoreum control), but also food and non-food odors according to their pubertal (penis/breast and pubic hair) development and general semantic knowledge about odors (operationalized as odor identification), controlling for age and perceived odor intensity. As a subsidiary aim, we examined variation in odor identification. We asked the children to self-stage themselves using drawings depicting Tanner's penis/breast and pubic hair stages of pubertal development, estimated their general semantic knowledge about odors with a Sniffin' Sticks identification test, and obtained their pleasantness and intensity ratings of body odor-related, food, a non-food smells. We found that the participants' ratings of the 16-androstenes and those of the perceptually similar odor of castoreum differed according to perceived intensity and, in the latter case, in boys vs. girls as well, but there were no influences of pubertal status or odor identification on the perceived pleasantness. Similarly, hedonic appraisal of non-food (but not food) odors was only influenced by perceived intensity. Regarding odor identification, differences between boys and girls were limited to younger children and did not become more marked throughout puberty. Perceived pleasantness of odors, irrespective of whether they are associated with body smells, food, or other, does not appear to vary across puberty, and boys and girls seem to achieve similar levels of semantic odor knowledge as they grow up.
Keywords: Cross-Sectional Studies; Humans; radost; Puberty; puberta; Hedonic; Czech Republic; Tanner stages; čich; mužské pohlaví; Česká republika; odoranty; Smell; průřezové studie; Odorants; Adolescent; čichová percepce; Olfactory Perception; ženské pohlaví; lidé; mladiství; Experience; dítě; Child; Male; Pleasure; Olfactory abilities; Female